Green Wrocław: Urban narratives of three post-war generations of Wrocław’s inhabitants - Biskupska, Kamilla (Polskie Studia Krajobrazowe, 2020)
This study is an invitation to reflect on issues that fall within the area of collective memory, an area that awaits further in-depth analysis. More specifically, this article is a proposal of a broader study on cultural landscape and places of memory than that which is dominant in the sociological literature. In particular, I examine the relationship between the inhabitants of the Polish “Western Lands” and the material German heritage of the cities in which they happen to live. I mainly focus on the relation between socially constructed memory and greenery—a “negligible” part of the space of human life. As I demonstrate in the article, the “green” narrations about Wrocław created after World War II are lasting and are still present in the stories of city’s inhabitants today.